2017
DOI: 10.1021/acs.iecr.7b03338
|View full text |Cite
|
Sign up to set email alerts
|

Robust Principal Component Pursuit for Fault Detection in a Blast Furnace Process

Abstract: Since blast furnaces are generally controlled by operators, the minor faults regarded as disturbances might be contained in the collected data matrix. This can severely affect sample distributions, which leads to arbitrary fault detection results using traditional data-driven methods. In this paper, a novel fault detection method named robust principal component pursuit (PCP) to handle minor faults is proposed. The minor faults are separated from columns and rows, respectively, in the training matrix via two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In Figure 12, it is shown that ACF and PACF of #1 BF are terminated within the confidence band at 5 and 2 orders respectively. Therefore, the prototype of this energy model for #1 BF can be set as ARMA (2,5). 2000 samples of seven BFs have been captured from an ironmaking plant with a production of ten million tons per year.…”
Section: B Practical Preparation For Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 12, it is shown that ACF and PACF of #1 BF are terminated within the confidence band at 5 and 2 orders respectively. Therefore, the prototype of this energy model for #1 BF can be set as ARMA (2,5). 2000 samples of seven BFs have been captured from an ironmaking plant with a production of ten million tons per year.…”
Section: B Practical Preparation For Optimizationmentioning
confidence: 99%
“…In 2019, China has become the largest iron and steel products supplier in the world, accounting for more than 53.26% of the total crude steel production. Therefore, the modeling and optimizing of ironmaking process would have significant benefits in economic development and environmental protection [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shang et al [8] developed a recursive transformed component statistical analysis (RTCSA)-based algorithms to monitor incipiently happened faults in the iron-making process. In addition, other kinds of PCA-based approaches have been introduced to monitor process faults, such as robust PCA [9] and convex hull-based PCA [10].…”
Section: Introductionmentioning
confidence: 99%
“…is a key unit. The blast furnace is a metallurgical furnace used in the manufacture of the industrial metals, and it works under high temperature and high pressure [6], [7]. The iron-making process consists of a blast furnace and five pieces of smelting auxiliary system equipment.…”
Section: Introductionmentioning
confidence: 99%